Disease-resistant watermelon variety against Fusarium wilt by remodeling rhizosphere soil microenvironment - Bingye Yang; Caipeng Yue; Chunhui Guo; Mingzi Zheng; Xiefeng Yao; Jinhua Xu; Sijie Huang; Mengmeng Yang (BMC Microbiology)
Abstract Background Rhizosphere microorganisms and their interactions play a critical role in enhancing plant disease resistance. Here, we found that the disease severity of the resistant variety LW025 showed a decreasing trend with the increase in continuous cropping cycles. However, the mechanisms underlying the reduction in disease severity during the continuous cropping of the resistant watermelon variety LW025, particularly its relationship with the rhizosphere microbiome, remain unclear. Results In this study, the transcriptome of different watermelon varieties after continuous planting in pathogen-containing and pathogen-free soils was analyzed. The results showed that only two genes expression showed significant differences in disease-resistant variety between healthy and diseased soils. Subsequently, we analyzed the differences of rhizosphere soil microbial communities after planting different watermelon varieties for three consecutive seasons, as well as the relationship between differential microorganisms and soil physiochemical properties and soil enzyme activity. The results demonstrated continuous cropping of the disease-resistant variety LW025 formed a rhizosphere microbiome different from the initial soil and susceptible variety. Specifically, fungal changes were primarily observed in Ascomycota and Chytridiomycota, while bacterial changes were mainly observed in Cyanobacteria and Gemmatimonadetes. The bacterial functions enriched in the rhizosphere of the resistant variety LW025 after continuous cropping were primarily associated with soil nitrogen cycling. Furthermore, the plant disease index showed a significant positive correlation with the available phosphorus and potassium content in the soil, while exhibiting a significant negative correlation with soil pH and catalase activity. Conclusions Overall, the reduction in disease severity associated with continuous cropping of the disease-resistant variety LW025 was more closely related to changes in the rhizosphere microecological environment. This study explained the mechanism of the resistant variety LW025 against Fusarium infection, and provided new prospects for the development of technologies based on rhizosphere microecological environment modification to improve the resistance of watermelon to Fusarium wilt.